2011
DOI: 10.1111/j.1601-183x.2011.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Association study of catechol-O-methyltransferase gene polymorphisms with schizophrenia and psychopathological symptoms in Han Chinese

Abstract: Although dysfunction of catechol-O-methyltransferase (COMT)-mediated dopamine transmission is implicatedin the etiology of schizophrenia, the human COMT gene has not been associated consistently with schizophrenia. The purpose of this study was to investigate whether the COMT gene is associated with the development of schizophrenia and whether the polymorphisms of this gene influence the psychopathological symptoms in patients with schizophrenia. Fourteen polymorphisms of the COMT gene were analyzed in a case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 14 publications
4
17
2
Order By: Relevance
“…A large number of human genetic association studies have been conducted to assess the association of COMT Val158Met with the risk of developing schizophrenia and other psychiatric disorders (Witte and Floel, 2012). Small increases in Val allele frequency have been reported in schizophrenia in some studies (Fan et al, 2005;Glatt et al, 2003), but in not others (Chen et al, 2011a;Nieratschker et al, 2010;Williams et al, 2005), while Met alleles are more frequent in some posttraumatic stress disorder (PTSD) populations (Boscarino et al, 2011;Kolassa et al, 2010;Valente et al, 2011). It is suggested that COMT predominantly affects dopamine metabolism in prefrontal cortex, where dopamine transporter expression is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of human genetic association studies have been conducted to assess the association of COMT Val158Met with the risk of developing schizophrenia and other psychiatric disorders (Witte and Floel, 2012). Small increases in Val allele frequency have been reported in schizophrenia in some studies (Fan et al, 2005;Glatt et al, 2003), but in not others (Chen et al, 2011a;Nieratschker et al, 2010;Williams et al, 2005), while Met alleles are more frequent in some posttraumatic stress disorder (PTSD) populations (Boscarino et al, 2011;Kolassa et al, 2010;Valente et al, 2011). It is suggested that COMT predominantly affects dopamine metabolism in prefrontal cortex, where dopamine transporter expression is relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses do not support the association with SZ (Fan et al, 2005;Munafo et al, 2005;Okochi et al, 2009). Several previous studies in the Han Chinese population failed to find a positive association with SZ (Fan et al, 2005;Yu et al, 2007;Kang et al, 2010;Chen et al, 2011); but these studies chiefly focused on only one SNP and the sample sizes involved were relatively small.…”
Section: Introductionmentioning
confidence: 56%
“…First, population stratification could lead to a resetting of population gene frequencies. The sample from Taiwan may not be representative of the entire Han Chinese population, because of a possible population stratification bias [Yeh et al, ; Chen et al, ]. Second, the BDNF genotypes can be regarded as trait‐dependent features, while the assessment of illness intensity by PANSS is state‐dependent.…”
Section: Discussionmentioning
confidence: 99%